Are first year students ready for a flipped classroom? A case for a flipped learning continuum - Louisa Tomas; Neus (Snowy) Evans; Tanya Doyle; Keith Skamp (International Journal of Educational Technology in Higher Education, 2019)
Abstract In our first year science and sustainability education subject, how to best support pre-service teachers to meet the conceptual demands of understanding important socio-ecological challenges such as climate change is a key focus of our teaching practice. In this multi-method case study, we explore how a flipped classroom supported students’ engagement and learning by way of an end-of-semester student survey, and a narrative account of our experiences, as educators, enacting the active learning strategies in class. Analysis of survey data showed that while students reported a high level of engagement with the videos and believed that they supported their learning, opinions were divided as to whether a flipped classroom was preferred over traditional lectures. Additionally, our reflections on how students engaged with the active learning strategies revealed that significant time was required at the start of class to review key concepts, as students appeared reluctant to engage independently with the planned activities–particularly those that involved more challenging science concepts. Informed by these findings, we propose a flipped learning continuum that fosters different levels of student-centred learning and autonomy, depending on students’ learning needs and their readiness for a flipped learning approach. In the context of the first year experience, specifically, some teacher-led instruction may be appropriate in a flipped classroom to support students’ transition to learning in higher education.